Critical Review: Review of the Efficacy, Safety, and Pharmacokinetics of Raltegravir in Pregnancy. (1st June 2016) - Maliakkal, Annabelle; Walmsley, Sharon; Tseng, Alice
Abstract : Abstract: Raltegravir was previously considered an alternative antiretroviral in pregnancy because of limited data, but recent pregnancy guidelines recommend raltegravir as a preferred integrase treatment option. Data from published articles and preliminary meeting reports between 2001 and July 2015 are reviewed. The literature includes a total of 278 maternal–infant pairs who received raltegravir during pregnancy. The standard raltegravir dose seems safe and effective in preventing mother-to-child transmission in late pregnancy presenters with unknown or unsuppressed viral load, or in multidrug resistance. Viral decay was rapid allowing most women to deliver at undetectable viral levels. Raltegravir was well tolerated, with the exception of a few cases of transient increases in maternal transaminases. No infant adverse effect was consistently reported. Existing data support the use of raltegravir in antiretroviral-naive and experienced pregnant women.